Is electricity storage green? A study on commercial buildings - ZHOU, Yangfang (Helen) (Institutional Knowledge at Singapore Management University, 2017)
Electricity storage facilities, such as industrial batteries, are considered the “holy grail” in decarbonizing the electrical grid. They are being widely installed in commercial buildings, e.g., hospitals and shopping centers. We model the problem of managing electricity storage in a commercial building as a Markov Decision Process. Our numerical results, based on models calibrated to the electricity load profiles of 100 commercial buildings in the U.S., show that for every electricity load profile, storage operation may increase carbon emissions.